The green dog : a mostly true story - Staples, Suzanne Fisher (Waterville, Me. : Thorndike Press, 2004)
During the summer before fifth grade, Suzanne, a daydreaming loner who likes to fish and walk through the woods, acquires a canine companion. Based on the author's childhood in northeastern Pennsylvania.
Keywords: Large type books; Dogs -- Fiction; Summer -- Fiction